POTENSI TEKNOLOGI BLOCKCHAIN DALAM PENGELOLAAN WAKAF TANAH: STUDI KOMPARATIF DI INDONESIA, MALAYSIA, TURKI, UEA, DAN QATAR - Yusnita; Astia, Mirza (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to explore the potential implementation of blockchain technology in the management of land waqf through a comparative analysis of five countries: Indonesia, Malaysia, Turkey, the United Arab Emirates (UAE), and Qatar. Globally, waqf management is undergoing a transformation from conventional systems to more transparent and accountable digital frameworks. Blockchain technology offers a decentralized data solution that can significantly reduce corruption, data duplication, and enhance accountability within waqf management organizations. This research adopts a qualitative approach, utilizing a literature review of official documents, academic journals, and reports from relevant institutions. The results reveal that each country has adopted different strategies for managing land waqf with varying levels of technological readiness. Turkey and the UAE have successfully integrated blockchain technology into their waqf systems, while Malaysia and Qatar are in the developmental phase. Indonesia, on the other hand, is still in the early stages of digitizing waqf. The study recommends a comprehensive roadmap for digitalizing waqf management based on blockchain technology in Indonesia, supported by appropriate regulations, human resources, and multi-sector collaboration.